Reformulation of the Prostitution Handling Model in Makassar City - Mutmainnah, Inayatul; Utomo, Jepri (Universitas Tanjungpura, 2024)
The aim of this research is to explore the model for handling prostitution in Makassar City and formulate recommendations for increasing its effectiveness. The fact that prostitution is still widely practiced despite efforts to eradicate it shows that there are weaknesses in the model that has been implemented. This research focuses on the Jalan Nusantara area using a descriptive qualitative approach. The findings of this study indicate the need to reformulate the handling of prostitution into a latent model that places a higher priority on sex workers' economic empowerment, human rights, policy advocacy, education, and counseling. This action is intended to reduce prostitution and improve the welfare of sex workers in Makassar City.